Translation Strategies for Cultural Terms in Mandarin Language in the Subtitles of the Film 'Aftershock' - Putri, Megawati; Nurochman, Nurochman; Hukmawati, Hukmawati (Institut Agama Islam Negeri Palopo, 2023)
Literary works are a medium used by authors to convey ideas and concepts. Literature usually takes the form of a socially-oriented work, such as films. Films are creations that narrate the social or cultural life of a society. This research aims to determine the classification and translation strategies of cultural terms in the film